2020
DOI: 10.11604/pamj.2020.37.364.25805
|View full text |Cite
|
Sign up to set email alerts
|

Impact de la COVID-19 sur la vaccination de routine en milieu hospitalier au Sénégal

Abstract: Introduction la pandémie COVID-19 a poussé le monde à mettre en œuvre des méthodes de prévention drastiques basées sur la limitation des mouvements des populations ayant un impact sur les politiques de santé publique comme la vaccination. L´objectif de ce travail était d´évaluer l´impact de ces mesures de prévention sur la vaccination de routine en milieu hospitalier depuis l´avènement de cette pandémie au Sénégal. Méthodes il s´agit d´une étude transversale rétrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The results of the present study reveal the immunisation coverage of BCG, MMR1, DPT-Hi+Hb 1 & 3 vaccines decreased with the appearance of the COVID-19 pandemic by an average decrease in coverage of 30%. Similar results were observed for studies conducted around the world ( 14 , 18 ). Similar results were also documented in Senegal where a drop of up to 50% per antigen was noted, and in the Mifi health district in Cameroon which showed that there is a drop in coverage of about 20% for BCG.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study reveal the immunisation coverage of BCG, MMR1, DPT-Hi+Hb 1 & 3 vaccines decreased with the appearance of the COVID-19 pandemic by an average decrease in coverage of 30%. Similar results were observed for studies conducted around the world ( 14 , 18 ). Similar results were also documented in Senegal where a drop of up to 50% per antigen was noted, and in the Mifi health district in Cameroon which showed that there is a drop in coverage of about 20% for BCG.…”
Section: Discussionsupporting
confidence: 89%
“…Vaccinators reported that some parents hesitated to have their girls vaccinated due to the risks of contracting COVID 19. Since the outbreak of COVID 19, a drop in the health seeking behaviour of communities has been reported in several settings (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood vaccinations (BCG, diphtheria-tetanus-pertussis, measles-rubella) have fallen sharply, leading to a worrying reduction in immunization coverage, raising fears of a resurgence of these diseases [36,38,45,58,80,89,108]. After the first wave, the trend reversed and returned to pre-March 2020 levels [68,89].…”
Section: Impact Of Covid-19 On Healthcare Accessmentioning
confidence: 99%
“…Access to healthcare was directly affected by the governmental measures taken to contain COVID-19 [24,37,38,44,48,57,69,70,84,94,99,106,108]. The implementation of physical distancing measures (containment, curfews, closure of businesses and places of entertainment or worship) impeded the movement of people and goods, and thus the seeking, provisioning, and delivery of healthcare, increasing tensions between healthcare personnel and patients [44,57,67,69,71,99,108,116].…”
Section: Impact Of Covid-19 On Healthcare Accessmentioning
confidence: 99%
See 1 more Smart Citation